Fulfillment and Complementarity: Reflections on Relationship in “Gifts and Calling” - Procario-Foley, Elena (Studies in Christian-Jewish Relations, 2017)
This article assesses how well two key terms in the 2015 Vatican statement, "The Gifts and the Calling of God Are Irrevocable" really contribute to the deepening of authentic friendship between post-Nostra Aetate Jews and Christians. Are the soteriologically and anthropologically freighted words "fulfillment" and "complementarity" so coded with a binary approach to relationship as to subvert this very laudable goal of the document? "Gifts and Calling" seems to want to define the Catholic-Jewish relationship as one of equals but its use of fulfillment language throughout calls into question whether it really envisions a relationship between equals. "Complementarity" is also problematic since that term almost always reinscribes an unequal power dynamic in which one side of the relationship, the “weaker” or “lesser” party fixed in a particular essence, needs to be completed by the other side. The article argues that questions of theological anthropology, teleology, morality, and theodicy need to be defined by each community on its own terms. It asks if there is a way to salvage the language of fulfillment and complementarity to foster a genuine mutuality between Jews and Christians as friends and pilgrims concerned for the reign of God in their distinct ways.